How CAGE, RAPS4-QF, and AUDIT Can Help Practitioners for Patients Admitted with Acute Alcohol Intoxication in Emergency Departments? - Brousse, Georges; Arnaud, Benjamin; Geneste, Julie; Pereira, Bruno; De Chazeron, Ingrid; Teissedre, Frederique; Perrier, Christophe; Schwan, Raymund; Malet, Laurent; Schmidt, Jeannot; Llorca, Pierre Michel; Cherpitel, Cheryl J. (Frontiers in Psychiatry, 2014)
Aims: To help clinicians to identify the severity of Alcohol Use Disorders (AUD) from optimal thresholds found for recommended scales. Especially, taking account of the high prevalence of alcohol dependence among patients admitted to the Emergency Department (ED) for acute alcohol intoxication (AAI), we propose to define thresholds of severity of dependence based on the AUDIT score. Methods: All patients admitted to the ED with AAI (blood alcohol level >0.8g/L), in a two-month period, were assessed using the CAGE, RAPS-QF and AUDIT, with the alcohol dependence/abuse section of the Mini International Neuropsychiatric Interview (MINI) used as the gold standard. To explore the relation between the AUDIT and the MINI the sum of the positive items on the MINI (dependence) as a quantitative variable and as an ordinal parameter were analyzed. From the threshold score (TS) found for each scale we proposed intervals of severity of Alcohol Use Disorders (AUDs). Results: The mean age of the sample (122 males, 42 females) was 46 years. Approximately 12 % of the patients were identified with alcohol abuse and 78 % with dependence (DSM-IV). Cut points were determined for the AUDIT in order to distinguish mild and moderate dependence from severe dependence. A strategy of intervention based on levels of severity of AUD was proposed. Conclusion: Different thresholds proposed for the CAGE, RAPS4-QF and AUDIT could be used to guide the choice of intervention for a patient: brief intervention, brief negotiation interviewing or longer more intensive motivational intervention.